2019
DOI: 10.3762/bjoc.15.1
|View full text |Cite
|
Sign up to set email alerts
|

Lectins ofMycobacterium tuberculosis– rarely studied proteins

Abstract: The importance of bacterial lectins for adhesion, pathogenicity, and biofilm formation is well established for many Gram-positive and Gram-negative bacteria. However, there is very little information available about lectins of the tuberculosis-causing bacterium, Mycobacterium tuberculosis (Mtb). In this paper we review previous studies on the carbohydrate-binding characteristics of mycobacteria and related Mtb proteins, discussing their potential relevance to Mtb infection and pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 125 publications
(124 reference statements)
0
9
0
Order By: Relevance
“…There is evidence to suggest that lectin-host interactions in Mtb are a potential mechanism to facilitate the establishment of infection. In this sense, it has been shown that lectins derived from Mtb could play an important role in infection in vivo ( Nogueira et al, 2010 ; Kolbe et al, 2019 ). It is likely that the deletion found in the Rv1419 gene in low prevalence isolates altered this host-pathogen interaction and therefore the ability of the mycobacterium to establish an infectious process.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence to suggest that lectin-host interactions in Mtb are a potential mechanism to facilitate the establishment of infection. In this sense, it has been shown that lectins derived from Mtb could play an important role in infection in vivo ( Nogueira et al, 2010 ; Kolbe et al, 2019 ). It is likely that the deletion found in the Rv1419 gene in low prevalence isolates altered this host-pathogen interaction and therefore the ability of the mycobacterium to establish an infectious process.…”
Section: Discussionmentioning
confidence: 99%
“…1, top left). Therefore, the role of Mtb glycosylation pattern and its impact in the recognition by the host immune system is still poorly clarified [24]. These evidence highlight the importance of further studies focused on how Mtb glycosylation regulate host–pathogen interactions and Mtb pathogenesis, envisioning novel strategies to stop the progression of tuberculosis, a disease that remains without cure.…”
Section: Pathogen‐associated Glycans In Infectious Diseases: a Source...mentioning
confidence: 99%
“…The recognition of ManLAM by DC-SIGN is associated with the ManLam capture and internalization by DC-SIGN on immature DCs, which is then targeted to lysosomes. This process results in IL-10 secretion, leading to suppression of DCs function [17,18], phagosome maturation of macrophages (MΦ) and CD4 + T-cell activation [24,25]. In fact, loss of O-mannosylation in these bacteria results in lower infection and proliferation rate in the host [26], as well as lower Tcell antigenicity [27], which highlight the relevance of ManLam glycans for Mtb immune escape.…”
Section: Bacterial Infectionsmentioning
confidence: 99%
“…Moreover, galectin-3 interacts with the master regulator KRAS, which, if mutated, is one of the main driver of various cancer types (Shalom-Feuerstein et al, 2008). Finally, lectins are also employed by highly pathogenic bacteria such as Mycobacterium tuberculosis, Pseudomonas aeruginosa, and uropathogenic Escherichia coli to facilitate cell adhesion and entry (Mitchell et al, 2002;Imberty et al, 2008;Hartmann and Lindhorst, 2011;Kolbe et al, 2019).…”
Section: Functions Traditionally Attributed To the Glycocalyxmentioning
confidence: 99%